Stapled Surgery for Hemorrhoidal Prolapse: From the Beginning to Modern Times - Sturiale, Alessandro; Fabiani, Bernardina; Menconi, Claudia; Cafaro, Danilo; Celedon Porzio, Felipe; Naldini, Gabriele (Reviews on Recent Clinical Trials, 2021)
Introduction: Hemorrhoidal disease is the most common proctologic condition in adults. Among the different surgical procedures, one of the greatest innovations is represented by the stapled hemorrhoidopexy. The history of this technique started with a single stapler use passing through a double stapler technique to resect the adequate amount of prolapse, finally coming to the use of high volume devices. Methods: Nevertheless, each device has its own specific feature, the stapler is basically made up with one or more circular lines of titanium staples whose height may be variable. The procedure is based on different steps: Introduction of the CAD, evaluation of the prolapse, fashioning purse string or parachute suture, the introduction of the stapler head beyond the suture, pull the wires through the window, close the stapler and keep pulled the wires of the suture held together with forceps, fire using two hands, open the stapler and remove it and check the staple line and then check the specimen. One of the latest innovations in stapled surgery is Tissue Selective Therapy. It is a minimally invasive procedure in which there is a partial circular stapled hemorrhoidopexy focused on the prolapsing piles with bridges of normal mucosa left. Results: Several studies have reported that SH is a safe and effective procedure to treat hemorrhoidal prolapse. It is a quicker procedure with a shorter hospital stay and earlier return to work if compared with the conventional treatment. This is due to less postoperative pain, postoperative bleeding, wound complications and constipation. Furthermore, the first generation devices had worse outcomes if compared with those of the new generation stapler that showed lower postoperative complication rates with better anatomical and symptomatic results. Conclusion: Stapled procedure for the treatment of symptomatic hemorrhoidal prolapse represents one of the most important innovations in proctology of the last century bringing with it the new revolutionary concept of the rectal intussusception as a determining factor involved in the natural history of the disease. Stapled hemorrhoidopexy marked an era in which the surgeon may offer the patients a safe, effective treatment with less pain and fast recovery.
Keywords: stapler complications